COVID-19: an outbreak in a nursing home in spring 2021: COVID 19 and Residential Homes - Castaldi, Silvana; Zani, Stefano; Lai, Alessia; Zehender, Gianguglielmo; Bergna, Annalisa; Boriello, Catia Rossana; Cereda, Danilo (Acta Biomedica Atenei Parmensis, 2021)
Introduction: Nursing home residents were the most vulnerable population to be affected by Coronavirus disease 2019 (COVID-19) in Italy. The Italian vaccination strategy decided to indicate them as the target population in the first phase of the massive vaccination campaign. We carried out an analysis on an outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection which occurred in a nursing home in northern Italy (Cremona) after the administration of the complete vaccination cycle affecting most of the guests of the structure. Methods: Data relating to the outbreak were obtained through the Regional Surveillance System for Infectious Diseases of Lombardia Region. Results: During the outbreak, among the 61 guests, 56 were vaccinated. Thirty four were found positive for COVID-19: 22 were asymptomatic, 12 were symptomatic and 4 died. The observed difference in the number of deaths between vaccinated and non-vaccinated subjects was significant. During the outbreak 104 healthcare workers (HCWs) were employed in the nursing home, only 66 were vaccinated. Eight HCWs were found COVID-19 positive, 4 of them were vaccinated and of female gender. Conclusions: Similarly to data reported in literature for described outbreaks, we observed that the vaccine is able to protect from the symptomatic form and a valid antibody response protect from a symptomatic disease. The low number of HCWs found positive indicates a correct use of individual protective devices.